2014
DOI: 10.4103/0972-124x.147408
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in Down′s syndrome subjects and systemically healthy subjects: A comparative clinical trial

Abstract: Objectives:To compare and quantify the presence of periodontal pathogens Aggregatibacter actinomycetemcomitans (Aac) and Porphyromonas gingivalis (Pg) in Down's syndrome (DS) and systemically healthy subjects with periodontitis and gingivitis.Materials and Methods:Fifty-nine age-matched subjects were categorized into four groups; Group I: DS subjects with gingivitis, Group II: DS subjects with periodontitis, Group III: Systemically healthy subjects with gingivitis and Group IV: Systemically healthy subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Among the twenty-six studies considered (all observational studies) published between 1968 and 2021, four were performed in the U.S.A. [56,58,65,72] and in Japan [59,63,66,69], three in Spain [15,51,52], Brazil [64,76,77] and in India [61,74,78], two in Sweden [57,67] and in Greece [68,70], and the remaining came from Germany [60], the Netherlands [67], Saudi Arabia [71], Mexico [73] and Iran [75]. Most observational studies were cross-sectional case/control studies comparing periodontal and microbial features of DSof various ages-with systematically healthy controls (HC), and/or subjects affected by mental retardations (MR) or cerebral palsy (CP).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the twenty-six studies considered (all observational studies) published between 1968 and 2021, four were performed in the U.S.A. [56,58,65,72] and in Japan [59,63,66,69], three in Spain [15,51,52], Brazil [64,76,77] and in India [61,74,78], two in Sweden [57,67] and in Greece [68,70], and the remaining came from Germany [60], the Netherlands [67], Saudi Arabia [71], Mexico [73] and Iran [75]. Most observational studies were cross-sectional case/control studies comparing periodontal and microbial features of DSof various ages-with systematically healthy controls (HC), and/or subjects affected by mental retardations (MR) or cerebral palsy (CP).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In 2014, Ahmed et al [74] from India compared and quantified the presence of two periodontal pathogens-A. actinomycetemcomitans and P. gingivalis in P-DS, G-DS, P-HC, and G-HC.…”
Section: Outcomementioning
confidence: 99%
“…Although aggressive periodontitis shows characteristic clinical features similar to those of the population who do not suffer from the syndrome, special features in periodontal pathogens have been identified, such as an increase in Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetemcomitans (Aac) in these patients compared to patients who do not suffer from trisomy of chromosome 21 (T-21) but who do present aggressive periodontitis [2]. Other species, such as Fusobacterium nucleatum (Fn), Prevotella nigrescens , or Actinomyces naeslundii , are also present in these individuals more often than in those who do not suffer from T-21 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative clinical trial found increased presence of P.g. in DS patients with periodontitis [ 18 ]. The role of INS can be supported by the fact that supernatants of potential periodontal pathogens, i.e., P.g.…”
Section: Discussionmentioning
confidence: 99%